A WORK-INTEGRATED LEARNING CASE STUDY INVESTIGATION OF AN INTERNSHIP PROGRAM AT A HIGHER LEARNING INSTITUTION IN SOUTH AFRICA - Khanyisile Yanela Twabu (Annals of the University of Craiova for Journalism, Communication and Management)
This study investigates the internship programmes offered at a higher learning institution by severely understaffed departments serving the institution with various tasks. This understaffing and backlog of workload creates a potential wealth of work-integrated learning (WIL) through internship programs, boosting student experience while improving institutional inefficiency. This study used qualitative data collection methods, including interviews and questionnaires. The study explores the internal experiences and challenges, highlighting the significant impact of internal contributions within severely understaffed departments. The WIL framework and the Knowledge Skills Abilities (KSA) model are employed to establish how universities implement curriculum design and pedagogies in their courses, programs, and modules to prepare students for the real world. The paper’s findings and conclusions recommend how institutions may improve the placement program.